Comparative Study of Protective Effect of Tomato Juice and N-Hexane Extract of Tomato on Blood Lipids and Oxidative Stress in Cholesterol-Fed Rats (Anwer Khan Modern Medical College Journal, 2017)
Background: Hyperlipidemia is a well-established risk factor in pathogenesis of atherosclerosis and atherosclerosisassociated conditions by enhancing oxidative stress. Dietary supplementation of tomato which is enriched with antioxidants especially like lycopene may therefore be effective in reducing oxidative stress during hyperlipidemic condition. The study evaluates and compares the protective effect of tomato juice and n-Hexane extract of tomato on oxidative stress in hyperlipidemic rats.Methodology: This experimental study was carried out among 42 rats divided in 7 groups. Rats were treated with 0.5% cholesterol (suspension of cholesterol powder in soybean oil) at a dose of 50 mg/ ml once daily through intragastric tube for 8 weeks. In other two groups of rats tomato juice (1 mg/kg) or n-Hexane extract of tomato (1 mg/kg) with 0.5% cholesterol were given orally once daily through intragastric tube for 8 weeks. Serum lipid profile, body weight, plasma malondialdehide (MDA) and erythrocyte reduced glutathione(GSH) levels were measured after 8 weeks in all the groups.Results: Administration of cholesterol caused significant increase (p